2021
DOI: 10.4103/jism.jism_19_21
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitude, and practice of Ayurveda pharmacists toward pharmacovigilance and adverse drug reaction reporting

Abstract: Background: Reporting adverse drug reactions (ADRs) is an important part of pharmacovigilance practice. Considering the significance of this area, the Ministry of AYUSH has introduced a new Central Sector scheme for promoting pharmacovigilance of Ayurveda, Siddha, Unani and Homoeopathy (ASU&H) drugs. Being key health-care professionals, physicians, pharmacists, technicians, and nurses have immense responsibility in effective implementation of pharmacovigilance programs through the surveillance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…[ 6 ] A published study among Ayurveda Pharmacists conclude that, even though there was a positive attitude toward ADR reporting, limited knowledge about the importance of the program needed to be addressed through educational initiatives, regular sensitization, and awareness programmes. [ 7 ] But, till date no such studies have been reported which could establish the cause and relationship of low reporting of ADR among Ayurveda Primary Care Physicians. Hence, this study was planned to assess the knowledge, attitude, and practice of Ayurveda teachers and practitioners of Gujarat State which may be further beneficial in taking necessary steps to improve the documentation and reporting culture.…”
Section: Introductionmentioning
confidence: 99%
“…[ 6 ] A published study among Ayurveda Pharmacists conclude that, even though there was a positive attitude toward ADR reporting, limited knowledge about the importance of the program needed to be addressed through educational initiatives, regular sensitization, and awareness programmes. [ 7 ] But, till date no such studies have been reported which could establish the cause and relationship of low reporting of ADR among Ayurveda Primary Care Physicians. Hence, this study was planned to assess the knowledge, attitude, and practice of Ayurveda teachers and practitioners of Gujarat State which may be further beneficial in taking necessary steps to improve the documentation and reporting culture.…”
Section: Introductionmentioning
confidence: 99%
“…Some adverse events have also been recorded as a result of insufficient regulatory measures, mostly uncontrolled distribution methods, such as mail order or online sales, poor quality control systems, and incorrect administration. 15 Researchers from reputable national research organisations have discovered that the polyherbal formulation AYUSH-64 can be used as a supplemental treatment for asymptomatic, mild and moderate Covid-19 infection. 16 At the National Institute of Nutrition in Hyderabad (NIN-ICMR), a pre-clinical investigation was also carried out to assess the immune-modulatory potential and safety/ toxicity of the AYUSH Kwatha formulation.…”
Section: Discussionmentioning
confidence: 99%
“…In order to protect the public's health, practitioners and healthcare professionals in ASU&H hospitals must now use extreme caution when it comes to drug safety monitoring. 6 Since pharmacovigilance is all about the science and activities relating to the detection, assessment, understanding and prevention of adverse effects of drugs or any other possible drug related problem 7 and ADR are the reaction that may be due to the drug itself or one of its metabolites, from an interaction between two or more drugs or between a drug and food. According to WHO "ADR is defined as a response to a drug that is noxious and unintended, and that occurs at doses normally used in human for the prophylaxis's, diagnosis or therapy of disease or for the modification of physiological function" 6,7 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Postgraduate students are essential part of a tertiary care centreand are the first contact person with the patient. Hence, this study was planned to assess the knowledge, attitude, and practice pharmacovigilance amongst Ayurveda postgraduate students and impact of an educational intervention on it, probably which will improve the practice of pharmacovigilance and drug safety [5,6].…”
Section: Introductionmentioning
confidence: 99%